HIKMAH PENGULANGAN AYAT FABIAYYI 'ALĀ'I RABBIKUMĀ TUKAŻŻIBĀN PERSPEKTIF TAFSIR AL-MISHBAH - Nur_Adella, Dwi; Rofii, M_Arwani (Jurnal Pendidikan Educandum, 2023)
The research in this thesis examined analytically the repetition of the verse fabiayyi 'al????ā'i rabbikumā tukażżibān in al-Raḥmān chapter. This verse is unique and special, which is repeated 31 times which made the reader thought about the repetition. Because of that the researcher wanted to study it to find out the intended meaning of the repetition of the verse. The researcher focused on the problems, namely, first about M. Quraish Shihab's interpretation of the repetition of the verse of fabiayyi 'al????ā'i rabbikumā tukadhdhibān in al-Raḥmān chapter in Tafsir Al-Mishbah. Second, about the wisdom behind the repetition of the verse of fabiayyi 'al????ā'i rabbikumā tukadhdhibān in al-Raḥmān chapter. The research method in this research is library research. The discussion in this study is descriptive-analytical, the researcher described the definitions, functions, types, and rules. In addition, the researcher explained the biography of Muhammad Quraish Shihab and his commentary. After that, the researcher conducted an analysis of the repetition of the fabiayyi 'al????ā'i rabbikumā tukażżibān in al-Raḥmān chapter using the perspective of Tafsir Al-Mishbah. The researcher found that the repetition of the verse fabiayyi 'al????ā'i rabbikumā tukadhdhibān in al-Raḥmān chapter according to Muhammad Quraish Shihab explained about the generosity of Allah SWT to His servants in giving favors, which aims as an affirmation to remind them of all the blessings that have been given to them God gave. The wisdom of repeating that verse is so that we are grateful for the favors that God has given us.